Preparation and characterisation of Pt-Ru/C catalysts for direct methanol fuel cells - Jackson, Colleen (Centre for Catalysis Research, 2017)
The direct methanol fuel cell (DMFC) is identified as a promising fuel cell for portable and micro fuel cell applications. One of the major benefits is that methanol is an energy dense, inexpensively manufactured, easily stored and transported, liquid fuel (Hamann et al., 2007). However, the DMFC's current efficiency and power density is much lower than theoretically possible. This inefficiency is predominantly due to the crossover of methanol from the anode to the cathode, Ru dissolution and Ru crossover from the anode to the cathode. In addition, the DMFC has a high manufacturing cost due to expensive catalyst costs and other materials. Catalyst expenses are further increased by catalyst loading due to low activity at the anode of the DMFC (Zhang, 2008). Hence, with increasing activity and stability of the Pt-Ru/C catalyst, catalyst expenditure will decrease due to a decrease in catalyst loading. In addition, performance will increase due to a reduction in ruthenium dissolution and crossover. Therefore, increasing the activity and stability of the Pt-Ru/C catalyst is paramount to improving the current DMFC performance and viability as an alternative energy conversion device. Pt-Ru/C catalyst synthesis method, precursors, reduction time and temperature play a role in the activity for methanol electro-oxidation and stability since these conditions affect structure, morphology and dispersivity of the catalyst (Wang et al., 2005). Metal organic chemical deposition methods have shown promise in improving performance of electro-catalysts (Garcia & Goto, 2003). However, it is necessary to optimise deposition conditions such as deposition time and temperature for Pt(acac)₂ and Ru(acac)₃ precursors. This study focuses on a methodical approach to optimizing the chemical deposition synthesis method for Pt-Ru/C produced from Pt(acac)₂ and Ru(acac)₃ precursors. Organo-metallic chemical vapour deposition (OMCVD) involved the precursor's vapourisation before deposition and a newly developed method which involved the precursors melting before deposition. An investigation was conducted on the effects of precursor's phase before deposition. The second investigation was that of the furnace operating temperature, followed by an exploration of the furnace operating time influence on methanol electro-oxidation, CO tolerance and catalyst stability. Lastly, the exploration of the Pt:Ru metal ratio influence was completed. It was found that the catalyst produced via the liquid phase precursor displayed traits of a high oxide content. This led to an increased activity for methanol electro-oxidation, CO tolerance and catalyst stability despite the OMCVD catalyst producing smaller particles with a higher electrochemically active surface area (ECSA).